All Days 2004
DOI: 10.4043/16840-ms
|View full text |Cite
|
Sign up to set email alerts
|

Technology Assessment of Deepwater Anchors

Abstract: The move of offshore oil and gas development into deepwater has required that the mooring systems for floating drilling and production platforms/vessels shift from catenary mooring systems to taut-leg mooring systems, requiring the need for a low cost deepwater anchor that can withstand major uplift mooring forces and be designed and easily installed to the design penetration with a high degree of reliability.Many deepwater anchor concepts have been proposed to meet the above requirements in recent years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…This confirms earlier promise seen by Ehlers [2] with other gravity installed anchors like Petrobras's Torpedo Anchor. Typically a set of eight anchors can be deployed from a typical AHV.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This confirms earlier promise seen by Ehlers [2] with other gravity installed anchors like Petrobras's Torpedo Anchor. Typically a set of eight anchors can be deployed from a typical AHV.…”
Section: Introductionsupporting
confidence: 86%
“…Assuming the surface undrained shear strength of the soil on this Mississippi Canyon location was around 50-psf and using Equation [2] in conjunction with the installation penetrations, Table 2 shows estimated undrained shear strength gradients for each anchor location. Using the calculated undrained shear strength gradient, the assumed surface shear strength of 2.4-kPa (50-psf), and the post Hurricane Gustav surveyed anchor penetrations, the axial capacity is estimated using Equation [3].…”
Section: Figure 6 -Installed Versus Post Hurricane Gustav Mooring Patmentioning
confidence: 99%
“…Although mostly used in soft clay, torpedo anchors have been used to moor mono-buoys and ships in shallow and deeper water in calcareous soils (Ehlers et al 2004). As they are being proven as an attractive and cost-effective alternative to more traditional anchoring solutions, with the progress of maturity, torpedo anchors will be applicable for other floating facilities, e.g.…”
Section: Applicationsmentioning
confidence: 99%
“…The rapidly growing hydrocarbon exploration and extraction activity in deep and ultradeep water (now approaching 3000 m) and in emerging provinces has necessitated the development of alternative anchoring concepts. Among others, DPAs are the newest (late 90's; Lieng et al 1999Lieng et al , 2000Medeiros 2001Medeiros , 2002 and are identified as the most promising concept due to (a) an economic, simple and quicker installation process performed by means of single anchor handling vessel (AHV) with no external energy source or mechanical operations required, (b) (and hence) a lower sensitivity to increasing water depth, (c) a high capacity under vertical and horizontal loading with no severe constraints about accurate positioning of the anchors on the sea bottom, (d) a flexibility in geometry that can accommodate a wide range of seabed strength (Medeiros 2002;Colliat 2002;Ehlers et al 2004), and (e) a relatively lighter weight and inexpensive fabrication. Medeiros (2001) reported a related cost savings of 30% compared with conventional anchoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…For TLPs, the loading angle θ of the pile is nearly zero, the pullout capacity is not affected by the location of the attachment point. For catenary and taut-wire mooring systems, the loading angle θ is typically in 45-60° (Randolph et al, 2005;Ehlers et al, 2004), the attachment point should be carefully selected.…”
Section: Failure Mode and Pullout Capacitymentioning
confidence: 99%